Parent and Adolescent Motivational Enhancement Intervention for Substance-Using, Truant Adolescents: A Pilot Randomized Trial. (21st December 2018) - Spirito, Anthony; Hernandez, Lynn; Cancilliere, Mary Kathryn; Graves, Hannah R.; Rodriguez, Ana Maria; Operario, Don; Jones, Richard; Barnett, Nancy P.
Abstract : The purpose of this article is to present the results of a treatment development study designed to examine the feasibility, acceptability, and preliminary efficacy of motivational enhancement therapy (MET) for substance using, truant adolescents plus the Family Check-Up (FCU) for parents. A randomized controlled trial was used to test the hypothesis that MET plus the FCU (MET/FCU) would lead to greater reductions in alcohol and marijuana use as well as truant behavior compared to a psychoeducation (PE) condition delivered to both adolescents and parents. Participants ( n  = 69; M age = 15.8 years) were 39% female, 59% White, and 31% Hispanic/Latino. Adolescents were referred from family court, from school truancy courts, from school counselors, or after presentations in high school health classes. Eligible participants reported using marijuana at least 3 times in the prior 90 days and a history of school truancy in the prior school year. The MET/FCU condition was found to be feasible to implement and was acceptable to both adolescents and parents. The PE condition was also found to be an acceptable and credible comparison condition by participants. Results at the 6-month follow-up favored MET/FCU over PE on days of marijuana use and number of times marijuana was smoked per day (medium effect), high volume drinking days and other drug use (small to medium effects), truancy indicators (small effects), parental monitoring (medium to large effects), and parent–teen problem solving (medium to large effects). A larger study to test the efﬁcacy of the MET/FCU appears warranted based on these promising findings.